“And then I check to see if it looks legit” – digital critical competence in teacher education - Leming, Tove; Johanson, Lisbeth Bergum (Frontiers in Education, 2023)
This study investigates pre-service teachers' understanding and use of their own digital critical competence. In the Norwegian teacher training programmes, pre-service teachers at all levels are required to develop critical reflection skills and learn basic digital skills. They have to be able to communicate digitally and at the same time be able to reflect on how developments in technology entail a growing need for critical assessment of digital media. Through a qualitative approach, we interviewed 17 social studies pre-service teachers at UiT The Arctic University of Norway and asked how they understand and use digital critical competence. Our study shows that the students' understanding of digital critical competence as a concept in the early stage of their education is mainly linked to source criticism and can largely be classified as a procedural understanding. A procedural approach means acting without any consideration of the underlying intentions; it requires little thought, and cognitive operations are ignored.More experienced pre-service teachers can link digital critical competence more clearly to the teaching profession and the school context and can reflect on didactic perspectives. They have a more norm-critical approach and question how information and knowledge are established.We find that they have developed a more critical and reflexive approach. The implication for teacher education is that digital critical competence should have a space in all subjects, not just social studies. This will help improve the quality of education and equip the pre-service teachers for everyday life as critical and reflexive teachers.